Application of nanocomposites for detection and removal glyphosate of wastewater: a review - Menezes, Luiza Bolla de; Rodrigo Bohn Rhoden, Cristiano; Leonardo da Silva, William (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
The global trade in pesticides is expanding in response to the demands of the agroindustry. Glyphosate serves as the primary active ingredient in numerous herbicides, typically applied through spraying. However, the glyphosate not taken up by the plants accumulates in the soil and wastewater, posing potential risks to the environment and human health by contributing to the development of various diseases. Nanocomposites are a class of materials that exhibit enhanced properties by the synergistic effects arising from the combination of their constituents. This emerging technology holds significant promise in the field of detecting and eliminating pesticides and other chemical compounds from wastewater. A bibliographic review was carried out in the Periódicos Capes database with the descriptors “nanocomposites” and “glyphosate” with the Boolean operator “and”. Articles available in full for consultation and original articles in English were included. Articles without full access and literature review articles were excluded. The timeline was selected automatically due to the articles found from 2017 to 2023. 42 articles were selected. Thus, we sought to evaluate the properties and efficiency of the nanocomposites used in the literature.